2016
DOI: 10.1152/ajpendo.00226.2015
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin improves response to glucose tolerance test in control and diabetic rats

Abstract: Neuregulin (NRG) is an EGF-related growth factor that binds to the tyrosine kinase receptors ErbB3 and ErbB4, thus inducing tissue development and muscle glucose utilization during contraction. Here, we analyzed whether NRG has systemic effects regulating glycemia in control and type 2 diabetic rats. To this end, recombinant NRG (rNRG) was injected into Zucker diabetic fatty (ZDF) rats and their respective lean littermates 15 min before a glucose tolerance test (GTT) was performed. rNRG enhanced glucose tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 56 publications
3
19
0
Order By: Relevance
“…Here, chronic NRG1 treatment did not alter basal and phosphorylated (Ser473 and Thr308) AKT level. These results are in accordance with the study by Lopez-Soldadό and colleagues who showed that acute injection of NRG1 does not activate AKT in skeletal muscle of lean and diabetic Zucker rats 46 . The other molecules evaluated (ERK1/2, AMPK, ACC and ACL) also were not affected by NRG1 treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Here, chronic NRG1 treatment did not alter basal and phosphorylated (Ser473 and Thr308) AKT level. These results are in accordance with the study by Lopez-Soldadό and colleagues who showed that acute injection of NRG1 does not activate AKT in skeletal muscle of lean and diabetic Zucker rats 46 . The other molecules evaluated (ERK1/2, AMPK, ACC and ACL) also were not affected by NRG1 treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Nrg1 treatment improved whole body glucose metabolism in db/db mice and diabetic rats [41], [42]. Whether Nrg4 may act directly on skeletal muscle to promote glucose uptake and utilization remains an important question to be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…All these ligands have been reported to play important roles in glucose transport, lipogenesis, or browning of the adipocytes, critical steps in glucose homeostasis and energy expenditure. Multiple studies have reported that NRG1 mediates glucose transport and improves glucose tolerance (14,26). Although NRG1 can bind to both ErbB3 and ErbB4, activation of ErbB4 was proven to be critical for the increased glucose uptake, as ErbB4-blocking antibodies impaired NRG1-induced glucose uptake (3).…”
Section: Introductionmentioning
confidence: 99%